B cells in acquired aplastic anemia and the exploratory role of rituximab: considerations in pediatric and female patients - Pan, Liangwu; Lin, Jianren; Zhou, Xiaobo; Zeng, Yanghui; Huang, Chuanming; Fu, Ying (Frontiers in Immunology, 2026)
Aplastic anemia (AA) is a severe hematological disorder characterized by bone marrow failure and peripheral pancytopenia. Immune dysregulation plays a central role in its pathogenesis. Recent studies highlight the critical involvement of activated B cells in the immunopathology of AA, influencing both disease onset and progression. Rituximab, a monoclonal antibody targeting CD20, demonstrates therapeutic potential by modulating B cell function. Notably, immune responses and clinical manifestations differ between pediatric and female patients, affecting the efficacy and safety profile of rituximab. This narrative review synthesizes current knowledge on B-cell involvement in AA, summarizes population-specific immunologic features, and appraises the exploratory evidence regarding rituximab use. By integrating mechanistic insights with available clinical observations, we highlight key gaps in the literature and outline priorities for future research to inform more individualized immunomodulatory strategies in AA.